Performance characteristics of Fungitell STAT™, a rapid (1→3)-β-D-glucan single patient sample in vitro diagnostic assay - D'Ordine, Robert L (Med Mycol, 2020)
Serum (1→3)-β-D-glucan (BDG), is an adjunct test in the diagnosis of invasive fungal disease (IFD). Fungitell STAT™, a facile, rapid, single patient option, executable for one or more patient specimens in approximately an hour, has been developed to address a need for rapid in-house testing. This method presents qualitative information concerning serum BDG levels, using an index value that allows the rapid categorization of patients as positive, negative, or indeterminate relative to serum BDG titer. The categorical and analytical performance of Fungitell STAT was evaluated. The categorical agreement between methods was established by testing patient samples which had been previously categorized with Fungitell. Receiver Operating Characteristic curves were used to identify cut-offs using 93 de-identified patient specimens. Subsequently, using these cutoffs, an independent group of 488 patient specimens was analyzed. Positive percent agreement (PPA) with, and without, indeterminate results was 74% and 99%, respectively. Negative percent agreement (NPA) was 91% and 98% with, and without, indeterminate results, respectively. Additionally, commercially available normal off-the-clot sera were spiked with Saccharomyces cerevisiae-derived (1→3)-β-D-glucan to produce analytical samples. Analytical reproducibility using spiked samples was excellent with 94% of the CV (coefficient of variation) values ≤10% among three independent laboratories. Good correlation with the predicate method was demonstrated with correlation coefficients of 0.90 or better with patient samples and 0.99 with spiked samples. The Fungitell STAT index assay provides a rapid and suitable method for serum BDG testing.